Structure and thermal behavior of EPDM/POSS composite fibers prepared by electrospinning. Issue 4 (1st August 2012) - Xue, Meng; Zhang, Xian; Ma, Lei; Gu, Zhen; Lin, Yongxing; Bao, Chao; Tian, Xingyou
Abstract Polyhedral oligomeric silsesquioxane (POSS)‐containing ethylene‐propylene‐diene monomer (EPDM) composite fibers have been prepared by electrospinning method, with an average diameter of micron grade and fibrous structural morphology. The results of transmission electron microscopy, Fourier transform infrared, and UV‐Vis spectra reveal that POSS moieties have been dispersed in polymer matrix homogeneously. A combination of thermogravimetric analysis and thermogravimetric‐differential scanning calorimetry (TG‐DSC) united analysis was used to investigate the thermal behavior of the resulting fibers at elevated temperatures. The results show that composites exhibited great increase of thermal decomposition temperature and large reduction of total heat release compared with pure EPDM. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013